Optimization of the infrared drying process for ultrasonic pretreatment of Hami-melon slices - LI Yi-can; ZHENG Xia; YAO Xue-dong; YANG Tao-qing; ZHANG Ji-kai (Shipin yu jixie, 2023)
Objective: This study aimed to the optimize infrared drying process of Hami-melon slices and improve quality and efficiency. Methods: Using ultrasonic treatment as a pretreatment method, the effects of drying temperature, slice thickness and ultrasonic treatment time on drying time, color difference value and vitamin C content were studied, and the drying time, quality and microstructure of the products were compared with those without ultrasonic treatment. Results: The optimal process parameters of ultrasonic pretreatment for infrared drying of Hami-melon slices were drying temperature 61 ℃, slice thickness 6 mm and ultrasonic treatment time 15 min. Under the control of these conditions, the drying time was 115 min, the color difference value was 13.79, and the vitamin C content was 112.1 mg/100 g. Compared with the untreated products, the drying time was shortened by 45.24%, the color difference was reduced by 13.38%, and the vitamin C content was increased by 16.71%. The microstructure showed that ultrasonic waves caused the expansion and contraction of the internal tissue of Hami-melon slices, and the structure was multi-channel. Conclusion: Ultrasonic treatment can be used as a pretreatment method to improve the infrared drying of Hami-melon slices, thereby improve the quality and efficiency of the drying process.